MONTELUCAST APPLICATION IN TREATMENT FOR BRONCHIAL ASTHMA OF VARIOUS SEVERITY - A.V. Kamaev; D.S. Korostovtsev (Union of pediatricians of Russia, 2007)
Occurrence of bronchial asthma is growing. The experts have proved its genetic and clinical heterogeneity. This is what also calls forth incomplete response to the conventional anti inflammatory medications. During asthma, dozens of various mediators take an active part in the pathogenesis of inflammation in the respiratory passages, including a set of c4, d4 and е4 leukotrienes, which causes contractions of the bronchi plain muscles. Among all the anti leukotriene medications ever studied for the sales in the Russian federation, the federal agencies approved of and registered zafirlukast and montelucast only. Montelucast is recommended in treatment for bronchial asthma of all the severity levels, as well as both as a medication to enhance the basic therapy and a medication for monotherapy, which is thanks to the data from a handful of multicentered, double, blind, placebo, controlled studies. The application of the peroral medications, montelucast in particular, may be a good alternative to the inhalant medications used among the patients with poor discipline and inhalation techniques (children, aged patients and etc.). When we speak of allergic rhinitis, montelucast application is essential to exclude polypragmasy, as well as for the initial asthma prevention.Key words: bronchial asthma, children, treatment, anti leukotrienes.